2021
DOI: 10.1007/s10518-021-01189-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk-targeted hazard maps for Spain

Abstract: Many studies have demonstrated that the design of structures in a region through the uniform hazard principle does not guarantee a uniform collapse risk. Even in regions with similar Peak Ground Accelerations (PGAs) corresponding to the same mean return period, the seismic risk in terms of collapse probability will be significantly different mainly due to the shape of the hazard curves as well as uncertainties in structural capacities. In this paper, risk-targeted hazard mapping is being explored in peninsular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…Some differences between the approaches therein [19], [26] and the one adopted in this paper are addressed in the following: (i) ASCE 7-16 provisions [26] are based on an acceptable p f of 1% in 50 years (2 × - 4 10 in one year), and P[C|IM D ] of 0.1. Herein, more stringent values of probabilities (i.e., lower p f and P[C|IM D ]) are explored, based on more recent risk-targeting studies conducted for other regions worldwide, especially low seismicity ones like Brazil [11]- [13];…”
Section: Risk-targeting Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…Some differences between the approaches therein [19], [26] and the one adopted in this paper are addressed in the following: (i) ASCE 7-16 provisions [26] are based on an acceptable p f of 1% in 50 years (2 × - 4 10 in one year), and P[C|IM D ] of 0.1. Herein, more stringent values of probabilities (i.e., lower p f and P[C|IM D ]) are explored, based on more recent risk-targeting studies conducted for other regions worldwide, especially low seismicity ones like Brazil [11]- [13];…”
Section: Risk-targeting Methodologymentioning
confidence: 99%
“…In this regard, risk-targeting approaches have emerged, as an alternative to the common Uniform Hazard maps, to provide Uniform Risk maps, i.e., design accelerations that provide a uniform failure probability across a region [10]. For example, Douglas et al [12] and Kharazian et al [13], using the risk-targeting methodology, identified different reductions or increase of the accelerations relative to the uniform hazard maps of 475 years RP depending on the seismicity of the site (i.e., low, moderate or high).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different structures are designed and analyzed using the same peak ground acceleration (PGA), but the possible risk of damage that occurs may not be the same, especially in the shape of the hazard curve and uncertainty in structural capacity. Of course, it depends on the condition of the structure, and the condition of the soil around the building [6].…”
Section: Causes Of Seismic Failuresmentioning
confidence: 99%